Reconceptualizing Domestic Roles: Integrating Prophetic Hadith and Psychological Well-Being for Working Women - Nurul Iffatiz Zahroh; Ahmad Fudhaili; Gazi Saloom; Muhammad Abdul Kharis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
Currently, the phenomenon of working mothers has become commonplace and no longer unfamiliar. However, in practice, many working mothers continously bear the responsibility of managing domestic work as an obligation considered absolute. This perception generally originates from interpretations of the Prophet’s hadith concerning women’s domestic roles. The present study aims to analyze the Prophet’s hadiths addressing women’s domestic responsibilities. Employing a qualitative approach and a library research method, the author reviews various sources regarding working mothers, their psychological impacts, and relevant Prophetic hadiths. The findings indicate that when the hadiths are read contextually, domestic roles are not necessarily an exclusive obligation for working mothers. Consequently, working mothers are afforded the space to actualize their potential fully in the public domain. Furthermore, the Prophetic traditions both endorse women’s engagement in the public sphere and demonstrate that Prophet Muhammad (peace be upon him) himself frequently assisted his wives with domestic tasks.